EFEKTIVITAS MEDIA SOSIAL INSTAGRAM PARIWISATA JEMBER SEBAGAI MEDIA PROMOSI PARIWISATA ONLINE - Windy Ayu Lestari; Ni Putu Eka Mahadewi; LGLK. Dewi (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
Promotional activities can be effective if the promotional purpose is achieved. To find out how effective the promotional media, it is necessary to measure the effectiveness of the media. This study aims to find out the effectiveness of Instagram social media @pariwisatajember as an online tourism promotion media by using the EPIC model method. Measurement of promotion effectiveness using EPIC model method is done by calculating first the average value of empathy dimension, persuasion dimension, impact dimension, and communication dimension, the determine the EPIC rate to find out how effective the promotion. The technique of determining samples in this study using the accidental sampling method is as many as 98 respondents. Data collection techniques using observation, interviews, questionnaires, literature, studies, and documentation. Data analysis techniques use descriptive quantitative analysis techniques, validity tests, reliability tests, and EPIC model analysis. The result showed that the effectiveness of Instagram social media @pariwisatajember as an online tourism promotion media showed effective result this shown by the measurement of the average value of the four dimensions and epic rate that within the effective scale range, where each value obtained is in empathy dimension of 3,63, persuasion dimension of 3,53, impact dimension of 3,54, communication dimension of 3,64 and EPIC rate of 3,58.